2020
DOI: 10.1164/rccm.202006-2309oc
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Generation from the Respiratory Tract with Various Modes of Oxygen Delivery

Abstract: Rationale: Aerosol generation with modes of oxygen therapy such as high-flow nasal cannula and noninvasive positive-pressure ventilation is a concern for healthcare workers during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. The amount of aerosol generation from the respiratory tract with these various oxygen modalities is unknown. Objectives: To measure the size and number concentration of particles and droplets generated from the respiratory tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
159
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(182 citation statements)
references
References 27 publications
18
159
2
1
Order By: Relevance
“…Recently, several publications report that NIRT are not actually aerosol generators, but aerosol dispersers. 8 And so, with the appropriate PPE, 4 , 5 and in the hands of experienced teams, it’s possible to reduce the intubation rate without seriously increasing the risk of nosocomial infections.…”
mentioning
confidence: 99%
“…Recently, several publications report that NIRT are not actually aerosol generators, but aerosol dispersers. 8 And so, with the appropriate PPE, 4 , 5 and in the hands of experienced teams, it’s possible to reduce the intubation rate without seriously increasing the risk of nosocomial infections.…”
mentioning
confidence: 99%
“…40 Higher gas flow rates generated more droplets, but NHFO actually reduced droplet/aerosol dispersion during sneezing, as the inward gas flow opposed nasal expiration. Gaeckle and colleagues 39 reported greater levels of aerosol and droplet generation with coughing but that NHFO did not increase this. These limited studies suggest NHFO may reduce droplet dispersion during sneezing and does not increase droplet dispersion during coughing compared with other oxygen delivery devices.…”
Section: Nhfo Aerosol and Droplet Generation Compared With Coughing Amentioning
confidence: 93%
“…38 A study of aerosol generation in healthy volunteers during normal breathing, found that NHFO did not increase aerosol generation compared with other modes of oxygen delivery (4 L min -1 simple nasal cannula (0.060 particles cm -3 ), 15 L min -1 face mask (0.059 particles cm -3 ), NHFO 30 L min -1 (0.046 particles cm -3 ), NHFO 50 L min -1 (0.041 particles cm -3 ), NIV 12/5 (0.056 particles cm -3 ) and NIV 20/10 cmH 2 O (0.057 particles cm -3 )). 39…”
Section: Nhfo Aerosol and Droplet Dispersion Compared With Other Oxygmentioning
confidence: 99%
“…We hypothesised that optimal use of potentially aerosol-generating procedures does not increase the risk of COVID-19 in HCWs when strict personal protection equipment (PPE) is applied ( Jansson et al, 2020 , Gaeckle et al, 2020 ).…”
mentioning
confidence: 99%
“…The protective effect of working at the COVID-ICU appears clinically meaningless, as such infection risk seems mainly influenced by circumstances outside the hospital. Even when the degree of aerosolisation is uncertain ( Gaeckle et al, 2020 ), the need for adequate HCW protection remains mandatory to ensure their safety.…”
mentioning
confidence: 99%